Uma investigação funcionalista das proposições relacionais estabelecidas por orações paratáticas aditivas e por orações paratáticas justapostas : relações retóricas de lista, de sequência, de condição e de resultado - Rúbio, Marília Gabriela (2011)
: This study aimed to investigate how the rhetorical relations of the list, the sequence, the condition and the results were established by means of coordinated additive and juxtaposed coordinated sentences and clause complexes formed by juxtaposed and additive coordinated sentences. This survey was based on Rhetorical Structure Theory (RST - Rhetorical Structure Theory), descriptive theory which aims to study the relationships established between the parts of a text. The research corpus consisted of five formal utterances of the type classes Database of Funcpar (Functionalist Research Group of North / Northwest of Paraná). The formal utterances were transcribed according to the pattern based on design standards NURC (Rio de Janeiro Oral Polite Norms Project), with some adjustments, and segmented into intonation units, according to Chafe (1987). After the Corpus analysis made, it was observed that, in relation to the list, the complex formed by two Oration Clauses were the most frequent and that And was the only connective used by informants conducts corpus for this relationship. The way-temporal correlation most widely used with the list relationship was about verbal forms is in the present tense. The instances of the relationship of the list were considered symmetrical i.e., the coordinated elements could switch positions without semantic alterations, with some exceptions: in one of the cases, there was a gradation of arguments, i.e., the last coordinated element retook the said elements, in the other, the coordinated elements could not be altered for the sake of reference. When investigating the sequence relationship, it was stated that the oration complex formed by two clauses were the most used by the informants of corpus and, when there was the addition among coordinated members, it was only used the connective AND. Regarding to the symmetry/asymmetry parameter, all occurrences of the corpus were considered asymmetric, i.e., the coordinated elements could not switch, since the sequence relationship presuppose the temporal subsequence. It was also observed that when the speaker recounted a past event (perfect and imperfect), it prioritized the sequence relationship due to their need to narrate or report an event that occurred that constantly, must follow the iconic order. The relation of condition, was expressed only by juxtaposed coordinated clauses, it means, when the coordinated sentences got together without using the connective, because despite syntactic coordination, there was a semantic subordination with casual value which allowed a conditional reading. This semantic subordination is the responsible for the asymmetry in all instances of that type of relationship in the corpus. The past event appeared in almost all instances, since the coordinated events followed an iconic sort that went from cause to consequence. In the other hand, the result relation was expressed by additive clauses and / or oration complex formed by addictive and juxtaposed clauses, since, to establish the relation of the outcome, it was mandatory the presence of connectives e aí , e daí , e com isso , aí and daí as MDs (Speech Markers). In what is considered the symmetry/asymmetry parameter, the clauses of results were considered asymmetric because the event conveyed by a clause was the result of an event conveyed by another clause. As regards the mode and tense, the past event appeared in virtually all instances, because the speaker was dealing with an event that occurred as a result of another.